BMI, Body Image, Emotional Well-Being and Weight-Control Behaviors in Urban African American Adolescents - Allen, Delenya; Belcher, Harolyn M.E.; Young, Allen; Gibson, Lillian Williams; Colantuoni, Elizabeth; Trent, Maria (International Journal of Child Health and Nutrition, 2016)
Importance: While urban African American adolescents face significant health disparities associated with overweight and obesity that follow them into adulthood; there is limited data on body image, emotional well-being, and weight control behaviors in this population to design effective public health interventions. Objective: This study was designed to understand the association of weight status to adolescent weight control, body image, and emotional well-being responses, in African American high school students. Design/Setting/Participants: The study cohort consisted of 776 students, mean age 15.8 years (±1.2). Data from Guidelines for Adolescent Preventive Services (GAPS) student surveys and anthropometric studies were collected at School-Based Health Centers. Main Outcome Measures: Associations between adolescent responses on the GAPS and body mass index (BMI) status (healthy weight: 5th to less than 85th percentile, overweight: 85th to less than 95th percentile, obese: 95th percentile or greater) were estimated using logistic regression and dose- response plots. Results: There were statistically significant associations between BMI category and weight control (ranging from a mean 5.18 to 7.68 odds of obesity) and body image (3.40 to 13.26 odds of obesity) responses. Responses to weight control and body image questions exhibited a dose- response for odds of overweight and obesity. Feelings of depressed mood were associated with obesity (1.47 times the odds of obesity compared to students who did not endorse depressed mood; 95% CI, 1.01 to 2.13) but not overweight status. Conclusion and Relevance: Overweight and obese urban African American adolescents are more likely to screen positively on weight control risk behaviors and negative body image questions than their normal weight peers. The weight control and body image measures on the GAPS may provide information to identify youth in need of services and those motivated for brief school-based weight control interventions.